2024
DOI: 10.1108/mrjiam-04-2023-1415
|View full text |Cite
|
Sign up to set email alerts
|

Social entrepreneurship in young students promoted by Latin American universities

Mónica Blanco-Jiménez,
Ana Gabriela Víquez-Paniagua,
Diana Maricela Vásquez-Treviño
et al.

Abstract: Purpose The purpose of this study is to analyze the strategies that allow sowing social entrepreneurship initiatives among young university students in Latin America. This study will also help to understand the different needs and expectations currently treated in higher education in developing its role as a promoter of entrepreneurship in students. Design/methodology/approach The study uses a multinomial logistic regression method analysis based on data collected through an online survey and applied to a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In the eighth paper, Blanco-Jiménez et al (2024) emphasize the significant role of LAC universities in promoting social entrepreneurship among students. Their research showed that educational institutions instill a mindset focused on addressing social and environmental challenges through innovative business solutions.…”
Section: Sustainable Entrepreneurship In Latin America and The Caribb...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the eighth paper, Blanco-Jiménez et al (2024) emphasize the significant role of LAC universities in promoting social entrepreneurship among students. Their research showed that educational institutions instill a mindset focused on addressing social and environmental challenges through innovative business solutions.…”
Section: Sustainable Entrepreneurship In Latin America and The Caribb...mentioning
confidence: 99%
“…Blanco-Jiménez et al (2024) suggest several policy recommendations to bolster universities' role in advancing social entrepreneurship. These include providing institutional support for social entrepreneurship programs, integrating social entrepreneurship across disciplines, evaluating program impacts through research and fostering partnerships with NGOs, businesses, and government entities (Yan et al , 2022).…”
Section: Sustainable Entrepreneurship In Latin America and The Caribb...mentioning
confidence: 99%
See 1 more Smart Citation